Relationship between Nutritional Knowledge, Physical Activity, Carbohydrates Intake and Fat Intake on Nutritional Status of Overweight Adolescents In Banjarmasin - RN, Amelia; Suminah, -; VI, Budiastuti (International Journal of Human and Health Sciences (IJHHS), 2023)
In Indonesia, the prevalence of overweight in adolescents has increased during the past ten years. Being overweight at a young age can lower the quality of life and cause early death at any age, affecting both men and women equally. This study analyzed the relationship between nutritional knowledge, physical activity, carbohydrate intake and fat intake in overweight adolescents in Banjarmasin. It used an observational study with the crosssectional approach. Purposive sampling was used to determine its samples, consisting of 64 respondents. The data on nutritional knowledge, physical activity, carbohydrate intake and fat intake were collected through structured questionnaires. Data of intake was collected by 3x24 hours food recall method on weekend and class days. They were analyzed by using the Pearson Product Moment statistical test. The results indicated that there is no relationship between nutritional knowledge (p=0,529) physical activity (p=0,218), carbohydrates intake (p=0,776) with nutritional status and there is relationship between fat intake with nutritional status (p=0.045) in overweight adolescents in Banjarmasin. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 144-147